A new technique of hindfoot reconstruction in chronic calcaneal osteomyelitis using the Ilizarov apparatus – a case series - Bassm Hamad Harahsheh; Asem Almajali; Al-Zaben, Raed; Jamal Rahaymeh, Anatoliy Sergeevich Sudnitsyn (Journal of the Pakistan Medical Association, 2022)
Background: Calcaneal osteomyelitis (OM) is a challenging disease. Traditional surgical management to cure the infection has a limited success in preservation of the hindfoot shape, function, and mechanical stability. Methods: Five patients in the age from 21 to 36 years with isolated total and subtotal calcaneal OM were treated with this technique. Complex treatment included two stages: 1) radical sequestrenecrectomy, antibiotic therapy for up to two weeks, and fixation of the foot in a favorable position with the Ilizarov fixator for wound healing as the first stage; 2) arthrodesis, reconstruction of the foot . The results of treatment were followed up in the immediate and long-term ( one to six years) periods . The infection process was completely arrested; its recurrence did not develop. Conclusion: .It is feasible to use Ilizarov distraction osteogenesis and transosseos osteosynthesis to fill in the bone and soft tissue defects for treatment of calcaneal OM. Continuous...